Integrating culturally informed approaches into physiotherapy assessment and treatment of chronic pain: a pilot randomised controlled trial. Issue 7 (5th July 2018) - Brady, Bernadette; Veljanova, Irena; Schabrun, Siobhan; Chipchase, Lucinda
Abstract : Objective: To evaluate patient engagement with, and the feasibility of, a novel, culturally adapted physiotherapy pain management approach. Design: A participant-blinded and assessor-blinded pilot randomised controlled trial. Setting: Outpatient physiotherapy departments at two public hospitals and one district pain clinic. Participants: Adults (n=48) with chronic musculoskeletal pain (daily pain >3 months), who self-identified as Mandaean, Assyrian or Vietnamese, were randomised to one of two physiotherapy treatment conditions. Interventions: 24 participants underwent combined group and individualised treatment described as 'culturally adapted physiotherapy', while 24 underwent evidence-informed 'usual physiotherapy care'. Both treatment arms consisted of up to 10 sessions over a 3-month period. Outcome measures: Patient engagement was measured via participant attendance, adherence and satisfaction data. Secondary outcomes included clinical measures of pain severity, interference and suffering, physical function and negative emotional state. Results: 96% of participants undergoing culturally adapted physiotherapy completed treatment, compared with 58% of the usual physiotherapy group. For the culturally adapted group attendance (87%±18%) and adherence (68%±32%) were higher relative to usual care (68%±32% and 55%±43%). Satisfaction was similar for the culturally adapted (82.7%±13.4%) and usual care (79.3±17.3) groups. For secondary outcomes, a significant between-group effect for pain-related suffering in favour of the culturally adapted group was observed with a medium effect size (partial η 2 0.086, mean 3.56, 95% CI 0.11 to 7), while results for pain severity, interference, physical function and negative emotional state were similar. Conclusions: Aligning treatment with the beliefs and values of culturally and linguistically diverse communities enhances patient engagement with physiotherapy. These results support the feasibility of a larger, multisite trial to determine if improved engagement with culturally adapted physiotherapy translates to improved clinical outcomes. Trial registration number: ACTRN12616000857404; Pre-results.